Pengembangan E-LKPD Berbasis STEM yang Berorientasi pada Keterampilan Proses Sains dan Pemahaman Konsep Peserta Didik pada Materi Bioteknologi di SMA Swasta Shafiyyatul Amaliyyah Medan - Sari, Siti; Idramsa; Hasairin, Ashar (Bioscientist : Jurnal Ilmiah Biologi, 2025)
This study aims to develop, validate, and examine the effectiveness of a STEM-based Biotechnology E-LKPD as a solution to the limitations of biology learning media, which are generally focused on printed texts and lecture methods. The research employed a Research and Development (R&D) approach using the 4D model (Define, Design, Develop, and Disseminate), involving expert validation, teacher responses, individual trials, and implementation in both experimental and control classes SMA Swasta Shafiyyatul Amaliyyah Medan. Validation results indicated that the product achieved very good criteria, with scores of 87.61% from material experts, 93.75% from learning and media experts, and 95.23% from language experts. Teacher responses to the E-LKPD reached 97.69% (very good), while students’ individual trial responses recorded 96.31% (very good). The implementation in the experimental class demonstrated a significant improvement in science process skills with an average percentage of 89.2%, compared to 61% in the control class. Furthermore, students’ conceptual understanding increased with an N-Gain score of 0.75 (high) in the experimental class, compared to 0.60 (medium) in the control class. These findings conclude that the STEM-based Biotechnology E-LKPD is valid, practical, and effective in enhancing students’ science process skills and conceptual understanding, aligning with the goals of the Merdeka Curriculum.